1995
DOI: 10.1007/bf01757698
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthase reduces Sephadex-induced oedema formation in the rat lung: Dependence on intact adrenal function

Abstract: In the present study we have investigated the effect of L-nitro arginine mono methyl ester (L-NAME), an inhibitor of nitric oxide (NO) synthase on Sephadex induced inflammation in the rat lung. Instillation of Sephadex into the airways induced an inflammatory reaction characterized by a long-lasting interstitial oedema, measured as an increase in lung weight, and an influx of inflammatory cells into the airways. L-NAME given s.c. prevented the increase in lung weight following Sephadex instillation. The inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We compared the effect of the nonselective NOS inhibitor, L-NAME, with the selective iNOS inhibitor, 1400W in a model of Sephadex-induced inflammation and found that L-NAME, and not 1400W, inhibit Sephadex-induced lung edema and lung tissue eosinophilia. This result is consistent with other workers who demonstrated that L-NAME reduced Sephadex-induced lung edema in the rat (Andersson et al, 1995) and inhibited antigen-induced airway microvascular permeability and eosinophilia in the guinea pig (Iijima et al, 1998) and eosinophilia in the sensitized and challenged rat (Ferreira et al, 1998). The studies described in this manuscript have taken these findings further by investigating the effects of a selective iNOS inhibitor 1400W, validating its activity in an LPS model of inflammation and testing its effectiveness in two models of eosinophilic lung inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…We compared the effect of the nonselective NOS inhibitor, L-NAME, with the selective iNOS inhibitor, 1400W in a model of Sephadex-induced inflammation and found that L-NAME, and not 1400W, inhibit Sephadex-induced lung edema and lung tissue eosinophilia. This result is consistent with other workers who demonstrated that L-NAME reduced Sephadex-induced lung edema in the rat (Andersson et al, 1995) and inhibited antigen-induced airway microvascular permeability and eosinophilia in the guinea pig (Iijima et al, 1998) and eosinophilia in the sensitized and challenged rat (Ferreira et al, 1998). The studies described in this manuscript have taken these findings further by investigating the effects of a selective iNOS inhibitor 1400W, validating its activity in an LPS model of inflammation and testing its effectiveness in two models of eosinophilic lung inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…These doses were the same as those previously reported by TSUKAGOSHI et al [10] in the rat. Similarly, the differential effects of aminoguanidine and L-NAME at these doses were shown by ANDERSSON et al [28] in Sephadex-induced inflammation in the rat lung. The present results show both aminoguanidine and L-NMMA to inhibit allergen-induced inflammatory cell influx and increase epithelial permeability in sensitized animals 24 h after allergen challenge, whereas the cNOS inhibitors produce no effect.…”
Section: Discussionsupporting
confidence: 67%
“…Inhibition of inducible nitric oxide synthase (iNOS) activity has been shown to have profound effect on edema formation in different models of inflammation [24]. Therefore, we think that, the first direction for future studies would be investigation of how exosomes affect COX2, PLA2, and iNOS signaling pathways at the site of acute inflammation.…”
Section: Discussionmentioning
confidence: 98%